EDUKASI PENGELOLAAN SAMPAH 3R DAN PRAKTIK DAUR ULANG (RECYCLE) SAMPAH ANORGANIK DI SD NEGERI KOTABARU KOTA TASIKMALAYA - Pratiwi, Mutia Hadi; Sundari, Wulan; Hairunnisa, Natasya; Sumartini, Yeni; Siti Khoeriah, Nening; Febriana, Nadia; Nurhasanah, Nenih; Izzati A. E, Nazma; Rahmadhina Ghinastiar, Nazwa; Indraswarni Anwar, Ultanika; Noor Annashr, Nissa (Jurnal Pengabdian Masyarakat Indonesia, 2024)
The waste problem is one of the environmental problems that has not been resolved properly in Indonesia. One of the efforts to reduce is by sorting waste based on its type so that it is easier to determine the next processing method and applying the 3Rs (reuse, reduce, and recycle) to prevent and reduce waste piles. The application of the 3R concept has proven to be an effective solution to minimize the negative impact of waste on the environment. The method used in this activity uses an interactive method. This activity involved measuring students' knowledge through post-test and post-test, the results of which were tested using the Wilcoxon test with a p-value of 0.000. The analysis showed a significant difference in the students' knowledge level, with more than 50 percent of the participants having increased knowledge, indicating the effectiveness of this educational program. Through this activity, it is hoped that a culture of environmental care will be created among students that can have a positive impact on the school environment and the surrounding community.